2020
DOI: 10.1097/01.ogx.0000669276.29328.3f
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Copy-Number Variations Associated With Early Pregnancy Loss

Abstract: (Abstracted from Ultrasound Obstet Gynecol 2020;55:96–104) Early pregnancy loss is most commonly caused by embryonic numerical and structural chromosomal abnormalities, which explain more than 50% of miscarriages. In more recent years, submicroscopic copy-number variations (CNVs) have also been identified in some early miscarriage specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…We found the overall prevalence of genetic variants to be significantly higher in fetuses with non-isolated CHD vs those with isolated CHD (38.6% vs 18.8%, P < 0.001). Among the genetic abnormalities, aneuploidy in particular was found to be significantly more common in fetuses with non-isolated CHD, a finding consistent with our previous work and that of others 11,19,22 . Interestingly, we did not observe a significant difference in the prevalence of CNV and sequence variants among cases with non-isolated compared with isolated fetal CHD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found the overall prevalence of genetic variants to be significantly higher in fetuses with non-isolated CHD vs those with isolated CHD (38.6% vs 18.8%, P < 0.001). Among the genetic abnormalities, aneuploidy in particular was found to be significantly more common in fetuses with non-isolated CHD, a finding consistent with our previous work and that of others 11,19,22 . Interestingly, we did not observe a significant difference in the prevalence of CNV and sequence variants among cases with non-isolated compared with isolated fetal CHD.…”
Section: Discussionsupporting
confidence: 92%
“…Two CMA platforms were introduced for detection of aneuploidies and CNVs: the HumanCytoSNP-12 array (Illumina, San Diego, CA, USA) and the Affymetrix CytoScan 750K array (Affymetrix, Santa Clara, CA, USA). Single nucleotide polymorphism array experiments and molecular karyotype analysis were performed as reported previously 19 . CNVs were reported according to the University of California Santa Cruz (UCSC) Human Genome build 19 and the National Center for Biotechnology Information (NCBI) build 37.…”
Section: Chromosomal Microarray Analysismentioning
confidence: 99%
“…A recent study performing a systematic analysis of copy number variations associated with early pregnancy loss showed that 22q11.2DS was the submicroscopic imbalance most frequent in miscarriage. Therefore, it was considered to be associated with early pregnancy loss, possibly due to major cardiac malformations incompatible with pregnancy progression and development [33]. While vanishing twin was a reason for exclusion in our study, cases may be missed if the gestational sac can no longer be identified.…”
Section: Discussionmentioning
confidence: 93%
“…24 Dai et al 25 found that the fetal chromosomal abnormality rate in firsttrimester spontaneous abortion was significantly higher than the second-trimester spontaneous abortion. Wang et al 26 reported that 309 genes were identified as potential miscarriage candidate genes by analyzing 5,003 miscarriage specimens. These studies found that chromosomal aneuploidy was one of the main genetic factors for abortion and also that some pCNVs were associated with miscarriage and stillbirth.…”
Section: Introductionmentioning
confidence: 99%